Recent Developments in Ventricular Assist Device Therapy - Angel Moctezuma-Ramirez; Haseeb Mohammed; Austin Hughes; Abdelmotagaly Elgalad (Reviews in Cardiovascular Medicine)
The evolution of left ventricular assist devices (LVADs) from large, pulsatile systems to compact, continuous-flow pumps has significantly improved implantation outcomes and patient mobility. Minimally invasive surgical techniques have emerged that offer reduced morbidity and enhanced recovery for LVAD recipients. Innovations in wireless power transfer technologies aim to mitigate driveline-related complications, enhancing patient safety and quality of life. Pediatric ventricular assist devices (VADs) remain a critical unmet need; challenges in developing pediatric VADs include device sizing and managing congenital heart disease. Advances in LVAD technology adapted for use in right ventricular assist devices (RVADs) make possible the effective management of right ventricular failure in patients with acute cardiac conditions or congenital heart defects. To address disparities in mechanical circulatory support (MCS) access, cost-effective VAD designs have been developed internationally. The Vitalmex device from Mexico City combines pulsatile-flow technology with a paracorporeal design, utilizing cost-effective materials like silicone-elastic and titanium, and features a reusable pump housing to minimize manufacturing and operational costs. Romanian researchers have used advanced mathematical modeling and three-dimensional (3D) printing to produce a rim-driven, hubless axial-flow pump, achieving efficient blood flow with a compact design that includes a wireless power supply to reduce infection risk. In conclusion, MCS continues to advance with technological innovation and global collaboration. Ongoing efforts are essential to optimize outcomes, expand indications, and improve access to life-saving therapies worldwide.